Counting missing women: A reconciliation of the "flow measure" and the "stock measure" - Cara Ebert; Stephan Klasen; Sebastian Vollmer (RWI - Leibniz-Institut für Wirtschaftsforschung, 2021)
Existing estimates of the 'tock of missing women' suggest that the problem is mostly concentrated in South and East Asia, and often related to sex-selective abortions and postbirth neglect of female children. In contrast, estimates of yearly excess female deaths, referred to as the 'flow of missing women', suggest that gender bias in mortality is much larger than previously found (about 4 to 5 million excess female deaths per year vs. around 100 million missing women in total), is as severe among adults as it is among children in India, and is larger in Sub-Saharan Africa than in South and East Asia. We argue that these findings largely rely on the choice of the reference standard for sex-specific mortality and an incomplete correction for different disease environments in the flow measure. When alternative reference standards are used, the results of the flow measure can be reconciled with previous findings of the stock measure. – – Bestehende Schätzungen des "Bestands an fehlenden Frauen" deuten darauf hin, dass sich das Problem vor allem auf Süd- und Ostasien konzentriert und häufig mit geschlechtsselektiven Abtreibungen und der Vernachlässigung von Mädchen nach der Geburt zusammenhängt. Im Gegensatz dazu deuten Schätzungen des jährlichen Überschuss von weiblichen Todesfälle, die als "Strom fehlender Frauen" bezeichnet werden, darauf hin, dass die geschlechtsspezifische Verzerrung der Sterblichkeit viel größer ist als bisher angenommen (etwa 4 bis 5 Millionen überzählige weibliche Todesfälle pro Jahr gegenüber etwa 100 Millionen fehlenden Frauen insgesamt), dass sie in Indien bei Erwachsenen ebenso schwerwiegend ist wie bei Kindern und dass sie in Subsahara Afrika größer ist als in Süd- und Ostasien. Wir argumentieren, dass die Ergebnisse des Strommaßes weitgehend auf den verwendeten Referenzstandard für die geschlechtsspezifische Sterblichkeit und eine unvollständige Korrektur für unterschiedliche Krankheitsumfelder zurückzuführen sind. Wenn alternative Referenzstandards verwendet werden, können die Ergebnisse des Strommaßes mit früheren Ergebnissen des Bestandsmaßes in Einklang gebracht werden.
Keywords: J16; D63; I10; 330; Missing women; gender bias; mortality; disease; age; Sub-Saharan Africa; China; India